Effect of spheroidized microstructure on the impact toughness and electrochemical performance of a high‐carbon steel. Issue 5 (8th December 2020) - Bairagi, Darothi; Munukuti, Venkataramana; Bhuyan, Pallabi; Saha, Rajib; Mandal, Sumantra
Abstract: The influence of cementite spheroidization on the impact toughness and electrochemical properties of a high‐carbon steel has been thoroughly investigated in this study. Heavy warm rolling, followed by 2 h of annealing, has resulted in near‐complete spheroidization, leading to a microstructure consisting of nano‐cementite globules dispersed in the ultrafine‐grained ferritic matrix. The Charpy impact test exhibited superior impact toughness with increased spheroidization. It is validated by the presence of abundant dimples in the fractographs of spheroidized specimens, in contrast to the as‐received one that experienced a brittle failure due to its lamellar pearlitic structure. Potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) carried out in a 3.5% NaCl solution revealed that the corrosion resistance of the alloy gets improved with the increase in the degree of spheroidization. This is attributed to the lower susceptibility of the spheroidized specimen to microgalvanic corrosion owing to the minimum area of contact between nano‐spheroidized cementite and ferrite, as elucidated with the help of EIS results aided by equivalent electrical circuit model. Abstract : Postdeformation annealing treatment resulted in near‐complete spheroidization. Enhanced spheroidization led to a superior impact toughness behavior. Pearlitic lamellae in AR specimen promoted severe microgalvanic corrosion. Spheroidization restricted microgalvanic corrosion by reducing the cathode/anode area. Spheroidized specimen showed a high charge transfer resistance and low capacitance.